2010
DOI: 10.1007/bf03214965
|View full text |Cite
|
Sign up to set email alerts
|

Age-hardening by miscibility limit in a multi-purpose dental gold alloy containing platinum

Abstract: This study examined the age-hardening by miscibility limit in a multi-purpose dental gold alloy containing platinum. The hardness increased rapidly in the initial stage of the aging process, reached the maximum value, then decreased continuously with aging time. The significant hardness increase resulted from the heterogeneous precipitation of the Pt-rich phase from the grain boundary of the Au-rich 1 matrix due to the miscibility limit of AuPt system. With increasing aging time, the fine Pt-rich precipitates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In the present study with Au-Ag-Pt alloy, the content of Au, together with Ag, was unequal in each layer of the lamellar structure, which was resulted from decreasing miscibility with decreasing aging temperature in Au-Pt and Ag-Pt systems [1,20].…”
Section: Element Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study with Au-Ag-Pt alloy, the content of Au, together with Ag, was unequal in each layer of the lamellar structure, which was resulted from decreasing miscibility with decreasing aging temperature in Au-Pt and Ag-Pt systems [1,20].…”
Section: Element Distributionmentioning
confidence: 99%
“…From the above, it can be concluded that the Pt-rich particle-like structures were composed of the major Pt-Au-rich 2 regions containing equal amounts of Zn and In and the minor Pt-Zn-rich 3 regions in which the contents of Zn were about three times of In, and where the separation of In and Zn progressed with aging time without apparent microstructural changes. In the study with an Au-Ag-Cu-Pt-In alloy, the Au-containing Pt 3 In particle-like structure was transformed into the Au-depleted particle-like structure containing relatively large amounts of Cu that was diffused from the Au-Ag-rich matrix, and which resulted from the overlapped miscibility limit of both Au-Pt and Ag-Cu systems [20]. However, in the present study with an Au-Ag-Pt-Zn-In alloy, such an Au-depletion in the Ptrich particle-like structure was not observed after transformation, as can be seen in Table 2(1,2).…”
Section: Element Distributionmentioning
confidence: 99%